Discovering the right key performance indicators in libraries: a review of literatures - Md Ishak, Amir Hussain; Sahak, Mohd Dasuki (2011)
This paper discusses the discovey of the right Key Performance Indicators (KPIs) in Malaysian libraries. As one of the measurement performance methodologies, KPIs are used to improved the overall organizational management and by applying the KPIs, it is considered an effort to transform libraries management towards excellence. The KPIs can be the key to organizations' success and for libraries to achieve their vision,mission,business strategy, objectives and targets. KPI Model was discussed by a few researchers in this paper to identify the right KPIs for libraries. The discussioncovers the library performance indicator standards by the International Organization for Standardization (ISO). The performance indicators described in this International Standard can be used effectively in the evaluation of libraries such as resources, access, infrastructure, use, efficiency and potentials and development. This paper also describes the flow of how to develop KPIs as proposed by Malaysian Administrative Modernization and Management Planning Unit, Prime Minister's Department Libraries need to identify their core business, core process and service before they identify the KPIs. The measures or indicators must be accepted, understood and owned across the organization in order to ensure that the performance measurement becomes effective. The discussion in this paper will help libraries understand and identify the right KPIs for libraries.